Prognostic significance of genotyping Helicobacter pylori infection in patients in younger age groups with gastric cancer. Issue 990 (18th April 2008) - Tiwari, S K; Manoj, G; Kumar, G Vasanth; Sivaram, G; Hassan, S I; Prabhakar, B; Devi, U; Jalaluddin, S; Kumar, K; Ahmed, S; Abid, Z; Habeeb, M A; et al.
Abstract : Background: Malignant tumours of the stomach are common, but the incidence of stomach cancer varies from country to country, probably a result of genetic, epigenetic and environmental factors. Stomach cancer often occurs in older people whose stomachs produce only small quantities of acid. Although infection with Helicobacter pylori has been proven beyond doubt in the aetiopathogenesis of various gastric disorders, not much is known about the genotypes of H pylori infection in early-onset gastric cancer. Aim: To ascertain the genotypes of H pylori in gastric cancer. Methods: Ninety-two patients were separated into three groups on the basis of their endoscopic findings: group 1, gastric cancer; group 2, gastric ulcer; group 3, non-ulcer dyspepsia. Gastric biopsy specimens were obtained for culture and DNA isolation; additional specimens were taken from subjects with gastric cancer for histopathological analysis. Amplification was performed using specific oligonucleotide primers to obtain genotypic data. Four samples from each group were randomly selected for sequence analysis. Results: Genotypic analysis showed cag T+ve/ hrg A+ve/ cag A+ve/ cag E+ve/ vac As1+ve to be highly prevalent in 79% of cases of H pylori infection. This genotype was found in 88% of subjects in group 1 and 78% in group 2. Intestinal-type adenocarcinoma was found in 35 subjects (83%), 32 (9%) of which harboured this genotype. Sequence analysis showed no significant strain-specific variations. Conclusions: Certain genotypes of H pylori have higher predictive value for the development of intestinal-type carcinoma at an early age. Genotyping of H pylori may well be a useful tool for screening people at increased risk of developing malignancy.